Adhesive gel with anisotropy as well as preparation method and application of adhesive gel

By designing an alternately arranged 2D adhesive strip arrays of adhesive strips and non-adhesive strips, using interface self-assembly and photopolymerization technology, the high aspect ratio and the anisotropic adhesive gel in the prior art are solved. The limitations of strength and preparation methods under the inclined 3D microcolumn structure achieve long-term stable and friction-resistant anisotropic adhesion performance.

CN119391335AActive Publication Date: 2025-02-07TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510012440.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-07
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing anisotropic adhesion gel requires extremely high body strength and strict preparation methods under the characteristics of high aspect ratio and inclined 3D micro-column structure, which limits the large-area preparation and application of materials, and has 3D micro-nano structure. It is susceptible to external forces to cause structure collapse and interface bonding fails.

Method used

A 2D adhesion strip array with alternately arranged adhesive strips and non-adhesion strips is designed to achieve anisotropic adhesion properties of the adhesion gel through interface self-assembly and photopolymerization techniques. Adhesive strips exhibit high adhesion and high friction, while non-adhesive strips exhibit low adhesion and low friction, adjusting the width, radian and angle of arc strips or sharp corner strips to achieve the Accurate regulation of anisotropic peeling force and friction force.

Benefits of technology

It achieves long-term, stable, friction-resistant anisotropic adhesion, simplifies the traditional preparation process, reduces strict restrictions on material processing, and expands the application range of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391335A_ABST
    Figure CN119391335A_ABST
Patent Text Reader

Abstract

The invention discloses anisotropic adhesive gel as well as a preparation method and application thereof. The adhesive gel is a 2D adhesive strip array formed by alternating adhesive strips and non-adhesive strips; wherein the adhesion strip is obtained by carrying out interface self-assembly and polymerization on a pre-polymerization solution rich in an adhesion gel monomer in a patterned region modified by n-octyltriethoxysilane; the non-adhesive strip is obtained by performing interface self-assembly and polymerization on a pre-polymerization solution rich in a non-adhesive gel monomer in a hydroxyl modified patterned region. Through the design, the adhesion gel can achieve the anisotropic adhesion effect, the research not only simplifies the complex preparation steps required by the traditional anisotropic adhesion material based on the 3D structure, but also achieves the long-acting, stable and friction-resistant anisotropic adhesion performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of functionalized gels, and more specifically, to an anisotropic adhesive gel and a preparation method and application thereof. Background Art

[0002] Anisotropy means that all or part of the chemical, physical and other properties of a substance change with the change of direction, and show different properties in different directions. For example, CN114989470A discloses a humidity-responsive anisotropic composite surface. The composite surface can have obvious soft / hard morphological transformation under different humidity conditions, and has both anisotropic / isotropic structural switching, thereby achieving controllable adhesion of the surface to objects and other properties, thereby achieving controllable adhesion to the adherend.

[0003] In recent years, the construction of patterns on the surface of gels to achieve excellent anisotropic adhesion has attracted widespread attention. Single-component gel materials cannot achieve effective anisotropic adhesion due to the uniformity of bulk and surface properties. At present, many studies are devoted to constructing gecko-like 3D cilia structures on the surface of gels to achieve anisotropic adhesion. However, for existing surface-patterned adhesive gels, the size of the structural units of their 3D cilia is usually at the micro-nano scale. These anisotropic adhesive gels require extremely high body strength and strict restrictions on material processing and preparation methods due to their high aspect ratio and inclined 3D micro-columns, which seriously restricts the large-scale preparation and application of materials. In addition, the fine 3D micro-nano structure can easily collapse under the action of external forces, resulting in interfacial adhesion failure. Therefore, it is of great significance to construct an adhesive pattern on the surface of the gel in one step to achieve long-term and stable anisotropic adhesion. Summary of the invention

[0004] Based on this, the first purpose of the present invention is to provide an anisotropic adhesive gel. The adhesive gel has adhesive strips and non-adhesive strips arranged alternately, wherein the adhesive strips exhibit high adhesion and high friction, while the non-adhesive strips exhibit low adhesion and low friction. This difference in structure and performance design enables the adhesive gel to exhibit anisotropic adhesive properties as a whole. This research not only greatly simplifies the complex and cumbersome steps involved in the traditional preparation of anisotropic adhesive materials for constructing 3D micro-nano structures, but also achieves long-lasting, stable, and friction-resistant anisotropic adhesive properties.

[0005] The second object of the present invention is to provide a method for preparing the adhesive gel as described above.

[0006] The third object of the present invention is to provide an application of the adhesive gel as described above in the preparation of a flexible adhesive gripper, an intelligent wearable device, and a wall-climbing robot.

[0007] In order to achieve the above first object, the present invention adopts the following technical scheme: The present invention discloses an anisotropic adhesive gel, wherein the adhesive gel is a 2D adhesive strip array composed of adhesive strips and non-adhesive strips alternately formed; Wherein, the adhesive strip is obtained by interfacial self-assembly and polymerization of a prepolymer solution rich in adhesive gel monomers in a patterned area modified with n-octyltriethoxysilane; The non-adhesive strip is obtained by interface self-assembly and polymerization of a prepolymer solution rich in non-adhesive gel monomers in a hydroxyl-modified patterned area.

[0008] Inspired by the unique arc-shaped adhesive sheet structure of the gecko's foot and its excellent anisotropic adhesive behavior, the adhesive strip array is designed to be alternatingly arranged arc strips or sharp-angled strips. Among them, the arc strips include adhesive arc strips and non-adhesive arc strips, and the sharp-angled strips include adhesive sharp-angled strips and non-adhesive sharp-angled strips. Through the above design, the adhesive gel can achieve the effect of anisotropic adhesion, that is, when peeling from the sharp-angled tip or arc-shaped top of the adhesive strip, the peeling force required to be applied is much greater than the force when peeling from the two arms of the sharp-angled strip or the two arms of the arc strip. Similarly, the friction force exhibited when sliding from the arc-shaped top or the sharp-angled tip of the adhesive strip to its two arms is much greater than the friction force from the two arms of the arc strip or the two arms of the sharp-angled strip to the arc-shaped top or the sharp-angled tip. In addition, by adjusting the width, curvature and sharp angle of the arc strip or the sharp-angled strip, precise regulation of anisotropic peeling force and friction can be achieved.

[0009] Further, the adhesive gel monomer is selected from one or more of isooctyl acrylate, dodecyl methacrylate, n-butyl acrylate, dopamine octyl ester, and oleic acid methacrylate; The non-adhesive gel monomer is selected from one or more of acrylamide, hydroxyethyl methacrylate, hydroxyethyl acrylate, N,N-dimethylacrylamide, methacrylamide, and N-isopropylacrylamide.

[0010] Furthermore, the adhesive strip and the non-adhesive strip are respectively in the shape of an arc strip or a pointed strip, and the adhesive strip and the non-adhesive strip have the same shape and their openings face the same direction, that is, the adhesive strip and the non-adhesive strip can both be arc strips or pointed strips; The width of each adhesive strip and each non-adhesive strip is 10µm-1.0cm respectively, which can achieve precise control of the width from micrometer scale to centimeter scale; The adhesive strip and the non-adhesive strip are in the shape of arc strips, and the arc range is 45-180°, such as 45°, 60°, 90°, 135°, etc.; The adhesive strips and the non-adhesive strips are in the shape of pointed strips, and the pointed angle range is 45-135°, such as 45°, 60°, 90°, 135°, etc., which can realize large-scale control of the curvature or angle.

[0011] Furthermore, the adhesive strip and the non-adhesive strip are in the shape of pointed strips, the peeling strength from the pointed tip of the adhesive strip is greater than the peeling strength from the two pointed arms, and the sliding friction from the pointed tip of the adhesive strip to the two pointed arms is greater than the sliding friction from the two pointed arms to the pointed tip.

[0012] Furthermore, the adhesive strip and the non-adhesive strip are in the shape of pointed strips, and the peeling force of peeling off from the pointed tip of the adhesive strip is 1.3-4.0 times the peeling force of peeling off from the pointed two arms, and the sliding friction force from the pointed tip of the adhesive strip to the pointed two arms is 1.2-3.0 times the sliding friction force from the pointed two arms to the pointed tip.

[0013] Furthermore, the adhesive strip and the non-adhesive strip are in the shape of arc strips, the peeling strength from the arc top of the adhesive strip is greater than the peeling strength from the arc two arms, and the sliding friction from the arc top of the adhesive strip to the arc two arms is greater than the sliding friction from the arc two arms to the arc top.

[0014] Furthermore, the adhesive strip and the non-adhesive strip are in the shape of arc strips, and the peeling force from the arc top of the adhesive strip is 1.2-5.0 times the peeling force from the arc two arms, and the sliding friction force from the arc top of the adhesive strip to the arc two arms is 1.2-3.0 times the sliding friction force from the arc two arms to the arc top.

[0015] In order to achieve the above second purpose, the present invention adopts the following technical solutions: The present invention discloses a method for preparing the adhesive gel as described above, comprising the following steps: 1) Preparation of patterned substrate The substrate is subjected to plasma treatment and n-octyltriethoxysilane modification treatment respectively according to a predetermined adhesive strip array pattern to obtain a patterned substrate with different modified areas arranged alternately; 2) Prepare a prepolymer solution rich in adhesive gel monomers and a prepolymer solution rich in non-adhesive gel monomers mixing an adhesion gel monomer, a first cross-linking agent, and a first photoinitiator to obtain a prepolymer solution rich in adhesion gel monomer; mixing the non-adhesive gel monomer, the second cross-linking agent and the second photoinitiator in solvent water to obtain a prepolymer solution rich in the non-adhesive gel monomer; 3) Preparation of adhesion gel A prepolymer liquid rich in adhesive gel monomers and a prepolymer liquid rich in non-adhesive gel monomers are mixed to obtain a mixed prepolymer liquid, 0.05-0.2 g of an emulsifier is added per 10 g of the mixed prepolymer liquid, and the emulsified solution is applied to a patterned substrate. The adhesive gel monomers and the non-adhesive gel monomers complete self-assembly and polymerization processes on the patterned substrate to obtain an adhesive gel.

[0016] In the present invention, the inductive effect of the hydrophilic / hydrophobic interaction at the solid / liquid interface is utilized, and the non-adhesive gel monomer and the adhesive gel monomer move directionally at the interface. The non-adhesive gel monomer is anchored in the plasma-treated substrate area through hydrophilic interaction, and the adhesive gel monomer is anchored in the n-octyltriethoxysilane-modified substrate area through hydrophobic interaction. After a one-step photopolymerization, the wettability pattern on the substrate surface can be perfectly transferred to the gel surface, thereby obtaining the designed adhesive strip array.

[0017] Furthermore, the molar ratio of the adhesive gel monomer to the non-adhesive gel monomer in the mixed prepolymer solution is 3:1-1:1, and illustratively, it can be 3:1, 2:1 or 1:1.

[0018] Furthermore, in the prepolymer solution rich in the adhesion gel monomer, the molar ratio of the adhesion gel monomer, the first cross-linking agent and the first photoinitiator is 0.05-0.20: 0.0010-0.0025: 0.0001-0.0002.

[0019] In the prepolymer solution rich in non-adhesive gel monomer, the concentration of the non-adhesive gel monomer is 0.5-3.0 mol / L, for example 2.5 mol / L, the content of the second cross-linking agent is 0.05-0.2 mg / mL, for example 0.15 mg / mL, and the content of the second photoinitiator is 0.05-0.2 mg / mL, for example 0.15 mg / mL.

[0020] Further, the first cross-linking agent is selected from one or more of triethylene glycol acrylate, diethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, and propylene glycol dimethacrylate; The first photoinitiator is selected from 2-hydroxy-2-methyl-1-phenylpropanone and / or 1-phenyl-1,2-propanedione-2-acetanilide; The second cross-linking agent is selected from N,N-dimethylbisacrylamide and / or N,N'-bis(2-aminoethyl)acrylamide; The second photoinitiator is selected from one or more of α-ketoglutaric acid, Irgacure 2959, acetophenone, and benzoylbenzophenone; The emulsifier is selected from one or more of polyvinyl alcohol, Tween, sodium lauryl sulfate and lecithin.

[0021] Furthermore, the polymerization process adopts light polymerization, the light power is 100-120W, and the light polymerization time is 40-60min.

[0022] Furthermore, when preparing the adhesive gel in the third step, the prepolymer liquid rich in adhesive gel monomers and the prepolymer liquid rich in non-adhesive gel monomers can be applied to the patterned substrate in sequence, or the prepolymer liquid rich in adhesive gel monomers and the prepolymer liquid rich in non-adhesive gel monomers can be mixed uniformly in advance and then applied to the patterned substrate together.

[0023] In order to achieve the third object, the present invention adopts the following technical solutions: The present invention discloses an application of the adhesive gel described above in preparing a flexible adhesive gripper, an intelligent wearable device, and a wall-climbing robot.

[0024] The beneficial effects of the present invention are as follows: The present invention firstly designs a predetermined pattern on the substrate by plasma modification and n-octyltriethoxysilane modification, and then uses the inductive effect of the hydrophilic / hydrophobic interaction of the solid / liquid interface to make the adhesive gel monomer and the non-adhesive gel monomer applied on the patterned substrate move in a directional manner, and the non-adhesive gel monomer will realize self-assembly in the patterned substrate area treated with hydroxyl modification due to the hydrophilic interaction, and the adhesive gel monomer will realize self-assembly in the patterned substrate area treated with n-octyltriethoxysilane modification due to the hydrophobic interaction, and then complete the emulsion interfacial polymerization by means of photoinitiation, and obtain an anisotropic adhesive gel with a 2D adhesive strip array. The preparation process is simple to operate and simplifies the complex preparation steps required to construct a 3D structure in order to achieve anisotropic adhesion.

[0025] By adjusting the ratio and composition of the emulsion, the width, curvature and angle of the strip, the anisotropic adhesive ability of the adhesive gel can be controlled. Studies have shown that the adhesive strips and non-adhesive strips in the adhesive gel prepared by the present invention are in the shape of pointed strips, and the peeling force of the pointed tip of the adhesive strip is 1.3-4.0 times that of the peeling force of the pointed arms, and the sliding friction force from the pointed tip of the adhesive strip to the pointed arms is 1.2-3.0 times that of the sliding friction force from the pointed arms to the pointed tip; the adhesive strips and non-adhesive strips in the adhesive gel prepared by the present invention are in the shape of arc strips, and the peeling force of the arc top of the adhesive strip is 1.2-5.0 times that of the peeling force from the arc two arms, and the sliding friction force from the arc top of the adhesive strip to the arc two arms is 1.2-3.0 times that of the sliding friction from the arc two arms to the arc top.

[0026] The adhesive gel prepared by the present invention can be widely used in flexible adhesive grippers, smart wearable devices, and wall-climbing robots. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.

[0028] Figure 1 A physical picture of the adhesive gel prepared in Example 1 is shown.

[0029] Figure 2 A schematic diagram showing the adhesive gel prepared in Example 2-1.

[0030] Figure 3 A schematic diagram showing a 90° peel force test of the adhesive gels prepared in Examples 2-1 to 2-5.

[0031] Figure 4 A schematic diagram showing the friction performance test of the adhesive gels prepared in Examples 4-1 to 4-4.

[0032] Figure 5 The optical image and microscopic scanning electron microscope image of the adhesive gel prepared in Example 4-4 after being rubbed 1000 times are shown.

[0033] Figure 6 A schematic diagram showing the adhesive gel prepared in Example 5-2. DETAILED DESCRIPTION

[0034] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0035] Example 1 1) Patterned substrate The present invention exemplarily provides a quartz substrate having alternating hydroxyl-modified strips and silane-modified strips, which is prepared by the following method steps: a. A cleaned quartz sheet with a size of 3cm*3cm*1mm was treated with oxygen plasma for 600s at a power of 300W. After the oxygen plasma treatment, the entire surface of the quartz sheet was modified with hydroxyl groups.

[0036] b. Spin-coat the photoresist S1805 onto the surface of the quartz wafer obtained in step a in the yellow light region at a spin-coating speed of 2000 rpm, an acceleration of 500 rpm / s, and a spin-coating time of 30 s. Then heat at 110°C for 30 s to cure the photoresist and store in a dark place.

[0037] c. In the yellow light area, the quartz sheet obtained in step b is covered with the designed strip mask and the photolithography step is performed with an exposure wavelength of 350nm and an exposure time of 12s. The size of the mask is 2cm*1cm, and the light-transmitting area and the light-impermeable area are alternating rectangular strips of 1cm*5mm.

[0038] d. The exposed quartz wafer obtained in step c was developed in a developer 300MIF, the development time was controlled to be 12s, and then rinsed with deionized water for 12s and dried with N2, and dried at 110°C for 30s. The quartz substrate in the unshielded area of ​​the mask was exposed, and the blocked area was covered with photoresist.

[0039] e. The quartz wafer partially covered by the photoresist obtained in step d was treated with oxygen plasma, wherein the treatment time was 600s and the power was 300W, so that the surface of the quartz wafer partially covered by the photoresist was modified with hydroxyl groups, and then the treated quartz wafer was placed in a vacuum oven, 75µL of n-octyltriethoxysilane was added next to the oven sample, the oven door was closed, and the reaction was heated to 80°C for more than 8 hours.

[0040] f. The quartz plate obtained in step e was cleaned with ethanol to remove the remaining photoresist, and then dried with N2 to obtain a patterned substrate having alternating hydroxyl-modified rectangular strips and silane-modified rectangular strips.

[0041] 2) Adhesion gel: rectangular strip array The present invention exemplarily provides an adhesive gel prepared on the basis of the above-mentioned patterned substrate, which is specifically prepared by the following method steps: a. Preparation of non-adhesive gel prepolymer solution: non-adhesive gel monomer acrylamide, photoinitiator α-ketoglutaric acid and cross-linking agent N,N-dimethylbisacrylamide are mixed to obtain non-adhesive gel prepolymer solution, wherein water is used as solvent, acrylamide concentration is 2.5 mol / L, α-ketoglutaric acid concentration is 0.15 mg / mL, and N,N-dimethylbisacrylamide concentration is 0.15 mg / mL; b. Preparation of an adhesion gel prepolymer: 0.15 mol of an adhesion gel monomer isooctyl acrylate was mixed with 0.0015 mol of triethylene glycol acrylate and 0.00015 mol of 2-hydroxy-2-methyl-1-phenylacetone to obtain an adhesion gel prepolymer; c. Mix the adhesive gel prepolymer liquid and the non-adhesive gel prepolymer liquid in a molar ratio of 2:1 to obtain a mixed prepolymer liquid, add 0.1 g of emulsifier PVA per 10 g of the mixed prepolymer liquid, and emulsify at a power of 585 W for 20 seconds to obtain a dispersed and stable mixed emulsion; d. Take 4g of the mixed emulsion and drop it on the patterned substrate obtained above, and put it into a photochemical reactor filled with N2. The non-adhesive gel monomers and adhesive gel monomers in the mixed emulsion are respectively aggregated on the surface of the quartz plate with alternating hydroxyl-modified strips and silane-modified strips, and then UV-polymerized for 40 minutes at 100W. Finally, the polymerized gel is separated from the quartz plate, and the gel without pattern on the edge is cut off to obtain an anisotropic adhesive gel with alternating adhesive gel strips and non-adhesive gel strips on the surface. The actual sample picture is shown in Figure 1 The prepared gel surface induces alternating adhesive rectangular strips and non-adhesive rectangular strips, each of which has a size of 1 cm*5 mm. Figure 1 The white part in the middle is the adhesion area, and the blue part is the non-adhesion area.

[0042] 3) 90° peel force test The adhesion test adopts the 90° peeling force test. In the present invention, all peeling force test experiments use the Mark-10ESM301 test bench. The test sample size is: 2cm×1cm. The polyimide tape is bonded to the back of the test sample as the backing material to prevent the test sample from stretching itself during the test. During the test, one end is clamped with a clamp, and the sample is peeled upward at a speed of 50 mm / min. The bottom test bench moves at the same speed to ensure a stable 90° peeling angle. The maximum value of force / width (width is 1 cm) is taken from the displacement-force curve obtained and recorded as the peeling force.

[0043] After testing, the peeling force of the adhesive strip in the adhesive gel prepared in Example 1 was 221.8±36.4 N / m, and the peeling force of the non-adhesive strip was 10.2±3.9 N / m.

[0044] Example 2-1 The process of preparing the patterned substrate is similar to that of Example 1, except that a patterned substrate having alternating hydroxyl-modified arcuate strips and silane-modified arcuate strips is obtained by changing the shape of the mask, the width of the arcuate strips is 10 µm, and the arc angle α is 90°.

[0045] The preparation of the adhesive gel is the same as in Example 1. The schematic diagram of the prepared adhesive gel is shown in Figure 2 , which has alternating adhered arcuate strips and non-adhered arcuate strips, each of which has a width of 10 µm and an arc angle α of 90°.

[0046] Example 2-2 The preparation process of the patterned substrate is referred to Example 2-1, except that a patterned substrate having alternating hydroxyl-modified arcuate strips and silane-modified arcuate strips is obtained by changing the shape of the mask, and the width of the arcuate strips is 100 µm and the curvature is 90°.

[0047] The preparation of the adhesive gel is the same as that of Example 2-1, which has alternating adhesive arcuate strips and non-adhesive arcuate strips, each of which has a width of 100 μm and an arc angle α of 90°.

[0048] Example 2-3 The process of preparing the patterned substrate is similar to that of Example 2-1, except that a patterned substrate having alternating hydroxyl-modified arcuate strips and silane-modified arcuate strips is obtained by changing the shape of the mask, and the width of the arcuate strips is 300 µm and the curvature is 90°.

[0049] The preparation of the adhesive gel is the same as that of Example 2-1, which has alternating adhesive arcuate strips and non-adhesive arcuate strips, each of which has a width of 300 μm and an arc angle α of 90°.

[0050] Embodiment 2-4 The process of preparing the patterned substrate is similar to that of Example 2-1, except that a patterned substrate having alternating hydroxyl-modified arcuate strips and silane-modified arcuate strips is obtained by changing the shape of the mask, and the width of the arcuate strips is 1 mm.

[0051] The preparation of the adhesive gel is the same as that of Example 2-1, which has alternating adhesive arcuate strips and non-adhesive arcuate strips, each of which has a width of 1 mm and an arc angle α of 90°.

[0052] Embodiment 2-5 The process of preparing the patterned substrate is similar to that of Example 2-1, except that a patterned substrate having alternating hydroxyl-modified arcuate strips and silane-modified arcuate strips is obtained by changing the shape of the mask, and the width of the arcuate strips is 5 mm.

[0053] The preparation of the adhesive gel is the same as that of Example 2-1, which has alternating adhesive arcuate strips and non-adhesive arcuate strips, each of which has a width of 5 mm and an arc angle α of 90°.

[0054] The adhesive gels prepared in Examples 2-1 to 2-5 were subjected to a 90° peeling force test. The test process was referred to Example 1. The peeling force test schematic diagram is shown in Figure 3 The results are shown in Table 1. The peeling force required for peeling from the top of the arc is significantly different from that required for peeling from the two arms of the arc strip, that is, anisotropic peeling force is achieved, and the anisotropy ratio is 1.4-1.8. This research has potential application prospects in flexible adhesive grippers, smart wearable devices, and wall-climbing robots.

[0055] Table 1

[0056] Example 3-1 The preparation process of the patterned substrate is referred to Example 1, except that a patterned substrate having alternating hydroxyl-modified arcuate strips and silane-modified arcuate strips is obtained by changing the shape of the mask, the width of the hydroxyl-modified arcuate strips is 300 µm, the width of the silane-modified arcuate strips is 300 µm, and the curvature is 90°.

[0057] The preparation of the adhesive gel is the same as that of Example 1, and it has alternating adhesive arcuate strips and non-adhesive arcuate strips, each of which has a width of 300 μm and an arc angle α of 90°.

[0058] Example 3-2 The process for preparing the patterned substrate refers to Example 3-1, except that a patterned substrate having alternating hydroxyl-modified arcuate strips and silane-modified arcuate strips is obtained by changing the shape of the mask, the width of the hydroxyl-modified arcuate strips is 1.5 mm, the width of the silane-modified arcuate strips is 300 µm, and the curvature is 90°.

[0059] The preparation of the adhesive gel was the same as that of Example 3-1, which had alternating adhesive arcuate strips and non-adhesive arcuate strips, each non-adhesive arcuate strip was 1.5 mm, each adhesive arcuate strip was 300 µm wide, and the arc angle α was 90°.

[0060] Example 3-3 The preparation process of the patterned substrate refers to Example 3-1, except that a patterned substrate with alternating hydroxyl-modified arcuate strips and silane-modified arcuate strips is obtained by changing the shape of the mask, the width of the hydroxyl-modified arcuate strips is 2.7 mm, the width of the silane-modified arcuate strips is 300 µm, and the curvature is 90°.

[0061] The preparation of the adhesive gel is the same as that of Example 3-1, which has alternating adhesive arcuate strips and non-adhesive arcuate strips, each adhesive non-arcuate strip is 2.7 mm, each adhesive arcuate strip is 300 µm wide, and the arc angle α is 90°.

[0062] Embodiment 3-4 The preparation process of the patterned substrate refers to Example 3-1, except that a patterned substrate having alternating hydroxyl-modified arcuate strips and silane-modified arcuate strips is obtained by changing the shape of the mask, the width of the hydroxyl-modified arcuate strips is 1 cm, the width of the silane-modified arcuate strips is 300 µm, and the curvature is 90°.

[0063] The preparation of the adhesive gel was the same as that of Example 3-1, which had alternating adhesive arcuate strips and non-adhesive arcuate strips, each adhesive non-arcuate strip was 1 cm, each adhesive arcuate strip was 300 µm wide, and the arc angle α was 90°.

[0064] The adhesive gels prepared in Examples 3-1 and 3-4 were subjected to a 90° peeling force test, and the results are shown in Table 2. There is a significant difference between the peeling force required when peeling from the top of the arc and the peeling force required when peeling from the two arms of the arc strip, that is, anisotropic peeling force is achieved, and the anisotropy ratio is 1.8-3.0.

[0065] Table 2

[0066] Example 4-1 The process of preparing the patterned substrate is similar to that of Example 1, except that a patterned substrate having alternating hydroxyl-modified arcuate strips and silane-modified arcuate strips is obtained by changing the shape of the mask, and the width of the arcuate strips is 300 µm and the curvature is 45°.

[0067] The preparation of the adhesive gel is the same as that of Example 1, and it has alternating adhesive arcuate strips and non-adhesive arcuate strips, each of which has a width of 300 μm and an arc angle α of 45°.

[0068] Example 4-2 The process of preparing the patterned substrate is similar to that of Example 4-1, except that a patterned substrate having alternating hydroxyl-modified arcuate strips and silane-modified arcuate strips is obtained by changing the shape of the mask, and the width of the arcuate strips is 300 µm and the curvature is 90°.

[0069] The preparation of the adhesive gel was the same as that of Example 4-1, and it had alternating adhesive arcuate strips and non-adhesive arcuate strips, each of which had a width of 300 μm and an arc angle α of 90°.

[0070] Example 4-3 The process of preparing the patterned substrate is similar to that of Example 4-1, except that a patterned substrate having alternating hydroxyl-modified arcuate strips and silane-modified arcuate strips is obtained by changing the shape of the mask, and the width of the arcuate strips is 300 µm and the curvature is 135°.

[0071] The preparation of the adhesive gel was the same as that of Example 4-1, and it had alternating adhesive arcuate strips and non-adhesive arcuate strips, each of which had a width of 300 μm and an arc angle α of 135°.

[0072] Example 4-4 The preparation process of the patterned substrate is similar to that of Example 4-1, except that a patterned substrate having alternating hydroxyl-modified arcuate strips and silane-modified arcuate strips is obtained by changing the shape of the mask, and the width of the arcuate strips is 300 µm and the curvature is 180°.

[0073] The preparation of the adhesive gel is the same as that of Example 4-1, which has alternating adhesive arcuate strips and non-adhesive arcuate strips, each of which has a width of 300 μm and an arc angle α of 180°.

[0074] The adhesive gels prepared in Examples 4-1 to 4-4 were subjected to a 90° peeling force test, and the results are shown in Table 3. The peeling force required for peeling from the top of the arc is different from the peeling force required for peeling from the two arms of the arc strip, resulting in anisotropic peeling force with an anisotropy ratio of 1.2-1.8.

[0075] Table 3

[0076] Friction performance test The adhesive gels prepared in Examples 4-1 to 4-4 were subjected to friction performance tests to evaluate the anisotropy of their frictional force. The test method is as follows: Figure 4 As shown, the adhesive gel to be tested has an adhesive strip facing up, and a cylindrical stainless steel probe with a diameter of 1 cm is used to contact the strip surface of the adhesive gel, and a pressure of 30 mN is applied. The movement direction of the probe is to slide from the top of the arc to the two arms, the sliding speed of the probe is 0.1 mm / s, and the sliding distance is 1 cm. The maximum force generated in the y direction during the sliding process is recorded as the friction force N1 from the top of the arc to the two arms, and the maximum force generated in the y direction during the sliding process in the opposite direction is recorded as the friction force N2 from the two arms to the top of the arc. The results are shown in Table 4. The friction force from the top of the arc to the two arms is different from the friction force from the two arms to the top of the arc, resulting in anisotropic friction, and the anisotropy ratio is 1.2-1.7.

[0077] Table 4

[0078] Wear stability The friction resistance of the adhesive gel prepared in Example 4-4 was tested as follows: a stainless steel cylindrical probe with a diameter of 1 cm was placed on the prepared adhesive gel with adhesive strips with a pre-pressure of 1 N, and moved parallel to the adhesive gel at a speed of 1 mm / s. After 1000 reciprocating movements, the sample was freeze-dried and the microstructure of the adhesive gel surface was observed. The results are shown in Figure 5The optical photographs and microscopic scanning electron microscope images showed that the boundary between the adhesive strip and the non-adhesive strip was still clearly visible after 1000 times of friction, and the adhesion force maintained the original level, proving that the anisotropic adhesive gel has excellent friction resistance and stability.

[0079] Example 5-1 The process of preparing the patterned substrate is similar to that of Example 1, except that a patterned substrate having alternating hydroxyl-modified sharp-angled strips and silane-modified sharp-angled strips is obtained by changing the shape of the mask, and the width of the sharp-angled strips is 300 µm and the angle is 45°.

[0080] The preparation of the adhesive gel was the same as in Example 1, which had alternating adhesive sharp-angled strips and non-adhesive sharp-angled strips, each of which had a width of 300 μm and an angle of 1. θ is 45°.

[0081] Example 5-2 The preparation process of the patterned substrate is similar to that of Example 5-1, except that a patterned substrate having alternating hydroxyl-modified sharp-angled strips and silane-modified sharp-angled strips is obtained by changing the shape of the mask, and the width of the sharp-angled strips is 300 µm and the angle is 90°.

[0082] The preparation of the adhesive gel was the same as that of Example 5-1, which had alternating adhesive sharp-angled strips and non-adhesive sharp-angled strips, each of which had a width of 300 μm and an angle of 1. θ is 90°, see the schematic diagram Figure 6 .

[0083] Example 5-3 The process of preparing the patterned substrate is similar to that of Example 5-1, except that a patterned substrate having alternating hydroxyl-modified sharp-angled strips and silane-modified sharp-angled strips is obtained by changing the shape of the mask, and the width of the sharp-angled strips is 300 µm and the angle is 135°.

[0084] The preparation of the adhesive gel was the same as that of Example 5-1, which had alternating adhesive sharp-angled strips and non-adhesive sharp-angled strips, each of which had a width of 300 μm and an angle of 1. θ is 135°.

[0085] The friction performance test method refers to Example 3-1, wherein the maximum force generated in the y direction during sliding is recorded as the friction force N3 from the sharp corner to the two arms, and the maximum force generated in the y direction during sliding in the opposite direction is recorded as the friction force N4 from the two arms to the sharp corner. The results are shown in Table 5. The friction force from the sharp corner to the two arms is different from the friction force from the two arms to the sharp corner, resulting in anisotropic friction, and the anisotropy ratio is 1.2-1.5.

[0086] Table 5

[0087] Example 6-1 The preparation process of the patterned substrate is referred to Example 1, except that a patterned substrate having alternating hydroxyl-modified sharp-angled strips and silane-modified sharp-angled strips is obtained by changing the shape of the mask, the width of the hydroxyl-modified sharp-angled strips is 1.5 mm, the width of the silane-modified sharp-angled strips is 300 µm, and the angle is 90°.

[0088] The preparation of the adhesive gel was the same as in Example 1, which had alternating adhesive angular strips and non-adhesive angular strips, each non-adhesive angular strip was 1.5 mm, each adhesive angular strip was 300 μm wide, and the angle was θ is 90°.

[0089] Example 6-2 The preparation process of the patterned substrate refers to Example 6-1, except that a patterned substrate with alternating hydroxyl-modified sharp-angled strips and silane-modified sharp-angled strips is obtained by changing the shape of the mask, the width of the hydroxyl-modified sharp-angled strips is 2.7 mm, the width of the silane-modified sharp-angled strips is 300 µm, and the angle is 90°.

[0090] The preparation of the adhesive gel was the same as that of Example 6-1, which had alternating adhesive sharp-angled strips and non-adhesive sharp-angled strips, each non-adhesive sharp-angled strip was 2.7 mm, each adhesive sharp-angled strip was 300 µm wide, and the angle was θ is 90°.

[0091] Example 6-3 The process for preparing the patterned substrate is similar to that of Example 6-1, except that a patterned substrate having alternating hydroxyl-modified sharp-angled stripes and silane-modified sharp-angled stripes is obtained by changing the shape of the mask. The width of the hydroxyl-modified sharp-angled stripes is 1 cm, the width of the silane-modified sharp-angled stripes is 300 µm, and the angle θ is 90°.

[0092] The preparation of the adhesive gel was the same as that of Example 6-1, which had alternating adhesive angular strips and non-adhesive angular strips, each non-adhesive angular strip was 1 cm, and each adhesive angular strip was 300 µm wide and at an angle of 90°.

[0093] The adhesive gels prepared in Examples 6-1 to 6-3 were subjected to a 90° peeling force test, and the results are shown in Table 6. The peeling force required when peeling from the top of the pointed angle is different from the peeling force required when peeling from the two arms of the pointed angle strip, resulting in anisotropic peeling force with an anisotropy ratio of 1.3-2.3.

[0094] Table 6

[0095] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. An anisotropic adhesive gel, characterized in that: The adhesive gel is a 2D adhesive strip array composed of adhesive strips and non-adhesive strips alternatingly; Wherein, the adhesive strip is obtained by interfacial self-assembly and polymerization of a prepolymer solution rich in adhesive gel monomers in a patterned area modified with n-octyltriethoxysilane; The non-adhesive strip is obtained by interface self-assembly and polymerization of a prepolymer solution rich in non-adhesive gel monomers in a hydroxyl-modified patterned area.

2. The adhesive gel according to claim 1, characterized in that The adhesive gel monomer is selected from one or more of isooctyl acrylate, dodecyl methacrylate, n-butyl acrylate, dopamine octyl ester, and oleic acid methacrylate; The non-adhesive gel monomer is selected from one or more of acrylamide, hydroxyethyl methacrylate, hydroxyethyl acrylate, N,N-dimethylacrylamide, methacrylamide, and N-isopropylacrylamide.

3. The adhesive gel according to claim 1, characterized in that The adhesive strip and the non-adhesive strip are respectively in the shape of an arc strip or a pointed strip, and the adhesive strip and the non-adhesive strip have the same shape and the openings thereof face the same direction; The width of each adhesive strip and each non-adhesive strip is 10µm-1.0cm respectively; The adhesive strip and the non-adhesive strip are in the shape of arc strips, and the arc range is 45-180°; The adhesive strips and the non-adhesive strips are in the shape of pointed strips, and the angle of the pointed strips ranges from 45° to 135°.

4. The adhesive gel according to claim 3, characterized in that The adhesive strip and the non-adhesive strip are in the shape of pointed strips, the peeling strength from the pointed tip of the adhesive strip is greater than the peeling strength from the two pointed arms, and the sliding friction from the pointed tip of the adhesive strip to the two pointed arms is greater than the sliding friction from the two pointed arms to the pointed tip; The adhesive strip and the non-adhesive strip are in the shape of arc strips, the peeling strength from the arc top of the adhesive strip is greater than the peeling strength from the arc two arms, and the sliding friction from the arc top of the adhesive strip to the arc two arms is greater than the sliding friction from the arc two arms to the arc top.

5. The adhesive gel according to claim 3, characterized in that The adhesive strip and the non-adhesive strip are in the shape of pointed strips, the peeling force from the pointed tip of the adhesive strip is 1.3-4.0 times the peeling force from the pointed arms, and the sliding friction from the pointed tip of the adhesive strip to the pointed arms is 1.2-3.0 times the sliding friction from the pointed arms to the pointed tip; The adhesive strip and the non-adhesive strip are in the shape of arc strips, and the peeling force from the arc top of the adhesive strip is 1.2-5.0 times the peeling force from the arc two arms, and the sliding friction force from the arc top of the adhesive strip to the arc two arms is 1.2-3.0 times the sliding friction force from the arc two arms to the arc top.

6. The method for preparing the adhesive gel according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) Preparation of patterned substrate The substrate is subjected to plasma treatment and n-octyltriethoxysilane modification treatment respectively according to a predetermined adhesive strip array pattern to obtain a patterned substrate with different modified areas arranged alternately; 2) Prepare a prepolymer solution rich in adhesive gel monomers and a prepolymer solution rich in non-adhesive gel monomers mixing an adhesion gel monomer, a first cross-linking agent, and a first photoinitiator to obtain a prepolymer solution rich in adhesion gel monomer; mixing the non-adhesive gel monomer, the second cross-linking agent and the second photoinitiator in solvent water to obtain a prepolymer solution rich in the non-adhesive gel monomer; 3) Preparation of adhesion gel A prepolymer liquid rich in adhesive gel monomers and a prepolymer liquid rich in non-adhesive gel monomers are mixed to obtain a mixed prepolymer liquid, 0.05-0.2 g of an emulsifier is added per 10 g of the mixed prepolymer liquid, and the emulsified solution is applied to a patterned substrate. The adhesive gel monomers and the non-adhesive gel monomers complete self-assembly and polymerization processes on the patterned substrate to obtain an adhesive gel.

7. The preparation method according to claim 6, characterized in that: The molar ratio of the adhesive gel monomer to the non-adhesive gel monomer in the mixed prepolymer solution is 3:1-1:

1.

8. The preparation method according to claim 6, characterized in that: In the prepolymer solution rich in adhesion gel monomer, the molar ratio of the adhesion gel monomer, the first cross-linking agent and the first photoinitiator is 0.05-0.20: 0.0010-0.0025: 0.0001-0.0002; In the prepolymer solution rich in non-adhesive gel monomer, the concentration of the non-adhesive gel monomer is 0.5-3.0 mol / L, the content of the second cross-linking agent is 0.05-0.2 mg / mL, and the content of the second photoinitiator is 0.05-0.2 mg / mL.

9. The preparation method according to claim 6, characterized in that: The first cross-linking agent is selected from one or more of triethylene glycol acrylate, diethylene glycol dimethacrylate, polyethylene glycol diacrylate, and polyethylene glycol dimethacrylate; The first photoinitiator is selected from 2-hydroxy-2-methyl-1-phenylpropanone and / or 1-phenyl-1,2-propanedione-2-acetanilide; The second cross-linking agent is selected from N,N-dimethylbisacrylamide and / or N,N'-bis(2-aminoethyl)acrylamide; The second photoinitiator is selected from one or more of α-ketoglutaric acid, Irgacure 2959, acetophenone, and benzoylbenzophenone; The emulsifier is selected from one or more of polyvinyl alcohol, Tween, sodium lauryl sulfate and lecithin.

10. Use of the adhesive gel according to any one of claims 1 to 5 in preparing flexible adhesive grippers, smart wearable devices, and wall-climbing robots.

Citation Information

Patent Citations

  • Preparation method and application of humidity response anisotropic composite surface

    CN114989470A

  • Adhesive material used for imitating gecko sole adhesive arrays and preparation method thereof

    CN103333495A

  • Gel with surface patterning, preparation method and application

    CN115043969A

  • Anisotropic controllable adhesion structure inspired by paper-cut and application thereof

    CN118685120A

  • Use of Shear to Incorporate Tilt into the Microstructure of Reversible Gecko-Inspired Adhesives

    US20150159067A1